Purwa Rupa Sistem Pengaman Sepeda Motor Berbasis IoT (Internet of Things - Juwariyah, Tatik; Widiyanto, Didit; Sulasmingsih, Sri (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2019)
The case of motorbike theft is one of the common problems in the community that needs to be found a solution. One of solutions to secure motorbikes from potential theft is to install smart vehicle technology (smart vehicl e). This paper describes the design of IoT vehicle safety systems using Arduino Mega microcontroller, fingerprint sensor, ESP8266 and Blynk applications on smartphones. For the experiment, this study uses an automatic transmission motorbike that represents the public motorcycle model. For research methods, this study uses three stages of design. The first stage is to compile the prototype hardware of a motorcycle security system using a fingerprint sensor, and a microcontroller. The second phase, IoT that uses a notification system on ESP8266-based smartphones and Blynk applications are designed. In the third stage, the security system and notification system sent via the smartphone are combined. In the results of the first phase of the trial, five people (whose fingerprints were registered and not registered) were involved to show the system was working as we expected. This means that even if the vehicle ignition is in the